Peluang Event Pariwisata Dalam Mengatasi Unsustainability Tourism di Pantai Kelapa Patimban Pusakanagara Kabupaten Subang - Arlianto, R. Hendro S.; Novianti, Evi; Endyana, Cipta (Jurnal Master Pariwisata (JUMPA), 2020)
This study discusses the holding of an "event" which is an opportunity to overcome the situation of unsustainability tourism in Pantai Kelapa Patimban, Subang. Furthermore, this study explains the importance of coordination with various interested parties in organizing "events". Descriptive studies are used to examine more in depth the situation of the Patimban Coconut Coast which is in a crisis situation after the mega International Port development project began in 2015. The results of the study in the discussion section led to a number of interesting findings, including the fact that the "event" must consider many things and is not as simple as determining the "event" in what field, who is the event host, and who is the target participant / visitor. There are many factors that must be considered to support the smooth implementation of "events" starting from the stage of pre-preparation (event designing), preparation (event preparation), the implementation (event execution), and evaluation (event evaluation). These factors can be learned from other disciplines.The author hopes that through this writing, the author can provide ideas or ideas to bring back the Coconut Patimban Beach to sustainability tourism in the future. Keywords: Tourism, sustainability tourism, unsustainable tourism, event, event tourism